THE POTENTIAL OF DAIYAH (WOMAN RELIGIOUS PREACHERS) TO HARNESS THE POWER OF RELIGIOUS PREACHING ON SOCIAL MEDIA - Badrah Uyuni; Mu’allimah Rodhiyana; Syarifah Soraya (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2023)
This article explores the evolving landscape of religious preaching in the digital age, focusing on women religious preachers. In today's world, religious discourse increasingly unfolds on various social media platforms, and the internet has become an integral part of daily life. Social media, once primarily a virtual social network, has now assumed a significant role in various aspects of society. Women religious preachers have taken center stage on social media platforms. They employ diverse communication styles and cover various topics, all aiming to promote good and prevent evil under Islamic values. This research employs qualitative methods and focuses on five prominent female daiyahs active on various social media platforms. We conducted an extensive online survey to assess their impact, audience engagement, and user preferences. Social media analytics tools were used to gather insights into reach, engagement, and emerging trends related to their content. Content analysis was conducted to unveil recurring themes, messaging strategies, and overall influence on their audience. Importantly, these women are engaging in religious discourse and shaping their Islamic identities through their distinct preaching styles. It discusses the adaptability of media technology in the Indonesian context, where global mobile phone practices have been localized and Islamized. This article sheds light on the profound impact of social media on religious preaching and underscores the crucial role of women religious preachers in this evolving landscape. It provides insights into their diverse activities and contributions to religious discourse in the digital age.